Benefits of caloric restriction in the myenteric neuronal plasticity in aging rats - Pereira, Joice N. B.; Mari, Renata B. [UNESP]; Stabille, Sandra R.; Faria, Haroldo G. de; Mota, Thais F. M.; Ferreira, Walter M. (Acad Brasileira De Ciencias, 2014)
Aging is a biologic process characterized by progressive damage of structures and functions of organic systems. In gastrointestinal tract, it can involve enteric nervous system, which plays an important role in digestion and absorption of nutrients, causing hastening of intestinal transit thus reducing its absorptive function. Caloric restriction has been used in several studies with the intention of delaying deleterious effects of aging. This study aimed to evaluate the effects of caloric restriction on myenteric neurons of ileum by aging in rats. 30 Wistar rats were grouped as follows: GI (animals aged 6 months fed with normal diet), GII (animals aged 18 months fed with normal diet) and GIII (animals aged 18 months subject to 31% of caloric restriction). The rats of the GI group were euthanized at 6 months of age and after experimental period of 12 months animals of the group GII and GIII were euthanized, the ileum of all groups were collected, measured and processed by NADPH-dp and Acetylcholinesterase. Quantitative analysis of neurons revealed that aging promotes the increasing of myenteric neurons NADPH-dp and reduces Acetylcholinesterase neuronal population. However, in the cellular profile area, were not observed significant differences between the groups. The caloric restriction has been efficient and can be used preventively because it minimizes quantitative changes associated with aging on ileum myenteric plexuses.

O envelhecimento é um processo biológico caracterizado por progressivos danos de estrutura e função dos sistemas orgânicos. No trato gastrointestinal, pode acometer o sistema nervoso entérico, o qual possui funções importantes na digestão e absorção de nutrientes causando aceleração do trânsito intestinal, reduzindo assim a sua função de absorção. A restrição calórica tem sido utilizada em vários estudos com a intenção de retardar os efeitos deletérios do envelhecimento. Este estudo teve como objetivo avaliar os efeitos da restrição calórica sobre os neurônios mioentéricos do íleo de 30 ratos durante o processo de envelhecimento. 30 ratos wistar foram agrupados da seguinte forma: GI (animais de 6 meses alimentados com dieta normal), GII (animais de 18 meses alimentados com dieta normal) e GIII (animais com idade de 18 meses com 31% de restrição calórica). Os ratos do grupo GI aos seis meses de idade e os animais do grupo GII e GIII foram eutanasiados após o período experimental de 12 meses, o íleo de todos os grupos foram coletados, medidos e processados pelas técnicas NADPH-d e acetilcolinesterase. A análise quantitativa dos neurônios revelou que o envelhecimento promove o aumento de neurônios mioentéricos NADPH-dp e reduz a população neuronal Acetilcolinesterase positiva. Entretanto, na área do perfil celular, não foram observadas diferenças significativas entre os grupos. A restrição calórica foi eficiente e pode ser utilizada como forma preventiva, uma vez que minimiza as alterações quantitativas associadas ao envelhecimento no plexo mioentérico do íleo.
Keywords: Aging; Caloric Restriction; Myenteric plexus; Small intestine; Envelhecimento; Restrição calórica; Plexo mioentérico; Intestino delgado